The relationship between job stress, job insecurity, work environment and employee performance : A study on industrial court employee in Kuala Lumpur - Siti Aisyah Munirah, Muhammad (2025)
Employee performance plays a crucial role in an organization's ability to achieve its goals. Therefore, it is important to assess how effectively individuals perform their duties. The study aimed to identify various factors that influence employee performance, with a particular focus on work stress, job safety, and the work environment. In this context, employee performance serves as a dependent variable, while work stress, job security, and work environment are considered independent variables. A total of 87 questionnaires were distributed to employees at the Kuala Lumpur Industrial Court using Google Forms. Data will be analysed using SPSS Version 27 through Multiple Regression Analysis to achieve the study objectives. Finally, this research aims to improve our understanding of the elements that can influence employee performance. The hypothesis on direct impressions was tested using multiple regression analysis. The findings of the study show that workplace stress, employee performance, job insecurity were found to have a significant positive relationship with employee performance. These findings give the impression that employee performance can be improved by providing less workplace stress, employee performance, and job insecurity that employees are able to handle. In this study, workplace stress, employee performance, job insecurity were seen to help employees to accumulate and use available resources to meet work demands which indirectly helped employee performance